A Critique on the Book The History of Educational Administration Viewed Through Its Textbooks - Rezvan Hosseingholizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The main purpose of this article is to analyze and critique the content of a historical work entitled The History of Educational Administration Viewed Through Its Textbooks. This book represents the reality of educational administration in a relatively long period of time in the mirror of public textbooks in this field and is a unique and valuable book by choosing a different tool for reviewing the historical course of educational administration. Therefore, while analyzing the structural, content and methodological features of this historical monument, its strengths and shortcomings were identified and extracted. The most important points in this book are the classification of historical courses in educational administration compared to similar classifications, the use of polysemous words in writing historical courses, ambiguity in distinguishing general and specialized textbooks of educational administration and internal inconsistency of the content of each course. Also, as a result of coping with the text, the quality of the Persian translation of the book was evaluated in terms of replacing the specialized Persian and correct equivalents, text, and psychological text, as well as the rules of writing and editing.